PERBEDAAN HASIL BELAJAR BERDASARKAN GESTURE WAJAH PADA PEMBELAJARAN MODEL STUDENT TEAMS ACHIEVEMENT DIVISION (STAD) KELAS VIII SMPN 1 PUNGGUR - Lestari, Widya Anggun; Suseno, Nyoto; Aththibby, Arif Rahman (JURNAL FIRNAS, 2023)
The purpose of this research is to know the difference of learning result based on face gesture on learning model of student teams achievement devision (STAD). This type of research is a quasi-experimental nature of qualitative research. The study population used the entire class VIII SMPN 1 Punggur. The research sample used 2 classes selected using purposive sampling that is class VIII-3 experiment (using STAD model) and VIII-4 control (lecture model). This research method uses test, observation and documentation. The data analysis used the average value of learning outcomes, gesture interpretation, and differences in learning outcomes based on face gestures. The first results of the study STAD learning model is used to improve students' learning outcomes prove by the average improvement of class learning results using STAD model 10.97, and classes using the lecture model 0.44, the two facial gestures shown during the learning experiment class and control class are different, the three learning outcomes based on face gesture on STAD learning model there is a difference. Suggestions for teachers to improve learners' learning outcomes are recommended using STAD learning model. STAD teacher learning model should pay attention to the gesture of his face. Teachers at the time of teacher learning should know the condition of learners to make learning more fun.